Devotion of Dissent: Contesting Hindutva in Bhakti Tradition - Das, Soma (Journal of Asian and African studies, 2024)
In the past few years, India has witnessed cataclysmic incidents of intermittent violence under the banner of Hindutva. Hindutva is a political ideology which works on extremist agenda to establish a homogenized cultural hegemony by focussing on exclusivist interests of Hindu majoritarian. It advocates revisionist attitude towards Hindu mythical figures by projecting them as prototypes of hypermasculinity to coax common Hindus with pseudo-patriotism. This article discusses on how Hindutva uses the principle of masculinity as its conceptual framework and its ramification on the socio-cultural fabric of India. It also deliberates on the fundamental essence of bhakti tradition, which largely contests Hindutva on ideological plane. Furthermore, it demonstrates the significance of bhakti literature in the present social context by alluding to the rich repository of saint poets whose verses critique Hindutva with a message of humanism.